1966
DOI: 10.1104/pp.41.8.1364
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory System of Rhodotorula glutinis I. Inhibitor Tolerance and Cytochrome Components

Abstract: Summary. Oxygen uiptake by the carotenoid-containinig yeast, Rhiodotorutl(a gliitinis was not affected by concentrationis of cyanide and antimycin A which completely inhibit the respiration of Saccharoinzyces ccrevisiae. The tolerance of R. glutitimis to these inhibitors was somewhat dependent on the age of the culttures. Reduced 1364 Materials and MethodsCuiltuires of R. glutiniis were grown with vigorotus aeratioin at 26 to 28°in 500 ml flasks cointainiing 100 ml of a gluicose, ammoniuim suLlfate, asparag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Growth in a medium amended with a Cyt inhibitor leads to 02 consumption which is fully resistant to cyanide and sensitive to SHAM. These results indicate a high level of activity of the alternate system and are similar to reports of CNinsensitive respiration in Neurospora crassa (12,15) and in Candida albicans (11) for which antimycin and SHAM have been used similarly to illustrate that the CN insensitivity is associated with an alternate respiratory system.…”
supporting
confidence: 87%
“…Growth in a medium amended with a Cyt inhibitor leads to 02 consumption which is fully resistant to cyanide and sensitive to SHAM. These results indicate a high level of activity of the alternate system and are similar to reports of CNinsensitive respiration in Neurospora crassa (12,15) and in Candida albicans (11) for which antimycin and SHAM have been used similarly to illustrate that the CN insensitivity is associated with an alternate respiratory system.…”
supporting
confidence: 87%
“…However, certain respiratory systems such as those of Rhodotorula glutinis (8,9) and Symplocarpus foetidus (skunk cabbage) (12) are insensitive to the antibiotic. Unestam and Gleason (13) showed that following an initial inhibition, antimycin A actually stimulates respiration of mycelia of a Saprolegnia sp.…”
mentioning
confidence: 99%
“…Green algae (22), yeast (1), many h'igher plant tissues (14), and animals (1) are also sensitive t'o these inhibitoors. There are, however, groups o'f closely related microorganisms which contain both sensitive and resiistan't species (18,21 found in both plants and animals. Not enough is known albout cytochrome proteins yet for theiir use in the study of evolution and phylogeny in the algae and in most groups o,f funigi.…”
Section: Discussionmentioning
confidence: 99%